Pengenalan Publikasi Ilmiah - Fitriani Nur; Suharti; Lisnasari Andi Mattoliang; Baharuddin; Badaruddin (KHIDMAH: Jurnal Pengabdian Masyarakat, 2023)
This service research aims to introduce scientific publications to participants in order to understand the form of scientific publications. Service research activities carried out by lecturers and students of the Mathematics Education Study Program in the form of socialization which took place face-to-face at the As'adiyah Sengkang Islamic Boarding School, involving 21 MTs / MAS As'adiyah Sengkang teachers. The data collection instrument uses a questionnaire through google form, then the data obtained is analyzed using descriptive analysis techniques. The results of this service research are considered useful, especially in the personal and professional lives of participants, and after participating in the socialization, participants will conduct research and publications.